The McGill Pain Questionnaire - Japanese Version, Reconsidered: Confirming the Reliability and Validity - Mamoru Hasegawa; Suguru Hattori; Keiji Ishizaki; Shosuke Suzuki; Fumio Goto (Pain Research and Management)
BACKGROUND: The McGill Pain Questionnaire (MPQ) is one of the most widely used instruments in the world to evaluate patients with chronic pain. However, differences in languages and cultural backgrounds have hindered its standardization in Japan.